2003
DOI: 10.1002/cplx.10087
|View full text |Cite
|
Sign up to set email alerts
|

Complex dynamics is abolished in delayed recurrent systems with distributed feedback times

Abstract: Feedback systems with a single delay time-as described by delay-differential equations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Eurich et al showed that dynamical systems converge to a stabilizing state and a simpler dynamical pattern with more uniformly distributed delay [10]. Several other studies showed similar results that distributed delay yields stabilizing state and simpler dynamical pattern [20,19,14]. Furthermore, networks with random delay were shown to have steady-state synchronization in coupled chaotic maps whereas those with fixed delay were shown to have chaotic synchronization [15].…”
Section: Research On Delaymentioning
confidence: 89%
See 1 more Smart Citation
“…Eurich et al showed that dynamical systems converge to a stabilizing state and a simpler dynamical pattern with more uniformly distributed delay [10]. Several other studies showed similar results that distributed delay yields stabilizing state and simpler dynamical pattern [20,19,14]. Furthermore, networks with random delay were shown to have steady-state synchronization in coupled chaotic maps whereas those with fixed delay were shown to have chaotic synchronization [15].…”
Section: Research On Delaymentioning
confidence: 89%
“…Networks must deal with delay which may vary for each connection. So far, only few studies have included time delay in dynamic network analysis [20,1,10,15,19,17]. These studies typically use delay differential equations.…”
Section: Introductionmentioning
confidence: 99%
“…Simply calculating the delay distribution can already provide great insights into brain function. For example, [51] showed that the complexity of network dynamics critically depends on the delay distribution. Also see [52] on the relationship between neuroanatomy and brain dynamics.…”
Section: Graph Theoretical Analysismentioning
confidence: 99%
“…Models with distributed delay have been developed mostly in applications to population biology and epidemiology. Examples include the work of Thiel et al [43] on how distributed delays may abolish complex dynamics present with fixed delays, work on blood cell population models [1,2,5], chemostat models [27,38,45,46], epidemic models [3], ecological models [4,11,19,36], and enzyme kinetics [20]. More examples can be found in the references within these papers.…”
Section: Introductionmentioning
confidence: 99%